Mural ilustrativo sobre los derechos de los Niños y niñas y adolescentes en los pasillos del MIES de la ciudad de Guaranda en el periodo 2015-2016 - Quinde Jaramillo, Fátima Lorena (2016)
The proposed degree work which has culminated in the creation of the mural on the rights of children and adolescents has arisen from the need to learn and know their rights as well as to recover their cultural values in order to create a positive impact on Bolivarian society in general, and Ecuadorian society specifically. The decision to create a caricature mural was the result of a desire to attract the interest of spectators and bystanders at the Ministry of Social Inclusion building in the city of Guaranda. This mixed-media work (acrylic on wood), is left as a permanent legacy for the city of Guaranda, and for the whole Country, and represents in graphic form all of the creativity, originality, and skill allowed by the art form. The first step in this project consists of the theoretical aspects which support and provide a foundational knowledge for the application of the artistic work. Topics such as history, background, and justification are addressed, and the originality, importance, necessity, and cultural contribution of the work are presented. The second stage of the project refers to the scientific theory, analysis, and study of contemporary caricature, as well as its history and evolution through the years within global and local art movements. The mural is unique in its originality and purpose, as it makes its message accessible to the blind, thus promoting the importance of teaching Braille to Bolivarian children and youth. Art is not exclusive, and it breaks down intangible barriers. University students have managed to obtain fundamental knowledge from their professors that allows them to create artistic works which can be appreciated by all people without exception. The technical process and methodology for the mural, including surface preparation, forming, and drying as well as the completion of a final report concludes the last stage of the execution of the mural. Photographs and descriptions of the technical processes which were performed throughout the project are included, successfully completing the objectives defined at the outset of this project. In pedagogy the area of artistic education provides the basis for the formation of sensitive, creative, and reflective people, with the ability to imagine multiple solutions to a single problem. In this way spectators participate indirectly in the creation of this type of project, and enjoy the manifestations of art and culture that are part of daily life for all human beings.